Selection of High Productivity New Lines of Winter Chickpea - Dilmurodov Sherzod Dilmurodovich; Kayumov Norboy Shakirjonovich; Boysunov Nurzod Bekmurodovich; Abdimajidov Jaloliddin Raxmatulla ugli; Shodiev Sherzod Shomiljon ugli; Juraev Husniddin Madatovich (Web of Journals Publishing, 2023)
Currently, the main part of the protein requirement of the human body is accounted for by peas and lentils, which are leguminous crops. In recent years, there have been many cases of seeds rotting without sprouting and plants dying due to severe damage caused by various diseases as a result of the planting of imported pea and lentil seeds by farms. It also leads to excessive costs as the cultivated pea and lentil stalks are not adapted to harvest by the machinery. In the study, 20 winter chickpea genotypes were evaluated and selected under irrigated field conditions. Winter chickpea genotypes were determined by parameters such as growth period.
Keywords: winter chickpea, genotype, variety, line, growing season, maturity.